(untitled) - Chen, Chaomei (London,New York, 2006)
This 2nd edition continues the unique and ambitious quest for setting information visualization and virtual environments in a unifying framework. Information Visualization: Beyond the Horizon pays special attention to the advances made over the last 5 years and potentially fruitful directions to pursue. It is particularly updated to meet the need for practitioners. The book is a valuable source for researchers and graduate students. This new edition is forwarded by Ben Shneiderman, University of Maryland
Keywords: Information visualization,Virtual reality,Đồ họa vi tính,Hiện thực ảo